THE 1.80-1.74-GA GABBRO-ANORTHOSITE-RAPAKIVI KOROSTEN PLUTON IN THE UKRAINIAN SHIELD: A 3-D GEOPHYSICAL RECONSTRUCTION OF DEEP STRUCTURE - Bogdanova S.V.; Pashkevich I.K.; Buryanov V.B.; Makarenko I.B.; Orlyuk M.I.; Starostenko V.I.; Legostaeva O.V.; Skobelev V.M. (My University, 2004)
The deep structure of the gabbro–anorthosite–rapakivi granite (“AMCG-type”) Korosten Pluton (KP) in the northwestern Ukrainian Shield was studied by 3-D modelling of the gravity and magnetic fields together with previous seismic data. The KP occupies an area of ca. 12,500 km2 and comprises several layered gabbro-anorthositic intrusions enveloped by large volumes of rapakivi-type granitoids. Between 1.80 and 1.74 Ga, the emplacement of mafic and associated granitoid melts took place in several pulses. The 3-D geophysical reconstruction included: (a) modelling of the density distribution in the crust using the observed Bouguer anomaly field constrained by seismic data on Moho depth, and (b) modelling of the magnetic anomaly field in order to outline rock domains of various magnetisation, size and shape in the upper and lower crust. The density modelling was referred to three depth levels of 0 to 5, 5 to 18, and 18 km to Moho, respectively. The 3-D reconstruction demonstrates close links between the subsurface geology of the KP and the structure of the lower crust. The existence of a non-magnetic body with anomalously high seismic velocity and density is documented. Most plausibly, it represents a gabbroic stock (a parent magma chamber) with a vertical extent of ca. 20 km, penetrating the entire lower crust. This stock has a half-cylindrical shape and a diameter of ca. 90 km. It appears to be connected with a crust–mantle transitional lens previously discovered by EUROBRIDGE seismic profiling. The position of the stock relative to the subsurface outlines of the KP is somewhat asymmetric. This may be due to a connection between the magmatism and sets of opposite-dipping faults initially developed during late Palaeoproterozoic collisional deformation in the Sarmatian crustal segment. Continuing movements and disturbances of the upper mantle and the lower crust during post-collisional tectonic events between 1.80 and 1.74 Ga may account for the long-lived, recurrent AMCG magmatism.
Keywords: Palaeoproterozoic; AMCG magmatism; Gravity; Deep-seismic sounding; Crust; Ukrainian Shield; Magnetism; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская